Description of Man and Nature in The Stories of Shukr Kholmirzayev - Ergasheva Marjona Qobilovna (European Science Publishing, 2023)
Man came into the world and lives while enjoying the beauty of nature. All the things we have created are : The birds and the beasts . All of them are the creations of God. And we humans have no right to be cruel to these creations. Nature and human interpretation in the works of well-known writer Shukr Kholmirzayev have always been the subject of various discussions. In this article, I also wanted to get acquainted with his creative works, express my thoughts and opinions to him,and show him the interrelationship between all things and mankind in the story.
Keywords: Man, nature, creatures, dependence, aesthetic pleasure.